2013
DOI: 10.1016/j.jhsa.2013.02.027
|View full text |Cite
|
Sign up to set email alerts
|

Reflections 1 Year Into the 21-Center National Institutes of Health–Funded WRIST Study: A Primer on Conducting a Multicenter Clinical Trial

Abstract: The Wrist and Radius Surgery Trial (WRIST) study group is a collaboration of 22 hand surgery centers in the US, Canada, and Singapore to showcase the interest and capability of hand surgeons to conduct a multicenter clinical trial. The WRIST study group was formed in response to the seminal systematic review by Margaliot et al. and the Cochrane report that indicated marked deficiency in the quality of evidence in the distal radius fracture literature. Since the initial description of this fracture by Colles in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The full study has been described in detail previously. 15 Participants of WRIST were enrolled at 24 sites in the United States, Canada, and Singapore from April 10, 2012, to December 31, 2016. Data used in these analyses were collected from April 24, 2012, to February 28, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The full study has been described in detail previously. 15 Participants of WRIST were enrolled at 24 sites in the United States, Canada, and Singapore from April 10, 2012, to December 31, 2016. Data used in these analyses were collected from April 24, 2012, to February 28, 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed protocols of the study design, enrollment, study flow diagram, and results of WRIST have been illustrated previously ( Supplement 1 ). 13 Written consent was obtained from all participants, and the WRIST protocol was approved by each center. This study adhered to the Strengthening the Reporting of Observational Studies in Epidemiology ( STROBE ) reporting guideline.…”
Section: Methodsmentioning
confidence: 99%
“…Other multisite studies have reported timelines of up to a year to obtain approval. 5–7 These data are evidence of the challenges investigators encounter while initiating trauma studies and the need for guidance.…”
Section: Introductionmentioning
confidence: 99%